Состояние социальной легитимности частной собственности как предмет эмпирического социологического анализа - Резник, В. (Социология: теория, методы, маркетинг, 2007)
The article contains the results of empirical analysis concerning current state and social-structural specificity of social legitimacy of the private property in the production factors within the present-day Ukrainian society. Basing on specially developed operational model and methods of multidimensional statistics, the author discovers a fact that private property in small business is socially legitimate now. However, one cannot assert this fact regarding the large scale industry and land where private property is to be considered as socially illegitimate. It is emphasized that current state of affairs may be changed because about one quarter of respondents have not yet taken their own position on private property.